PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS LEARNING CYCLE 5-E PADA POKOK BAHASAN LAJU REAKSI - Ratih Nurbintari; Elva Yasmi Amran; Erviyenni Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research has been to produce LKPD based on learning cycle 5-e on the subject of valid reaction rate based on feasibility of content, language, kegrafisan, and presentation. The research was conducted in Chemistry Education Department of PMIPA FKIP University of Riau on May 16, 2017. Research is done by research and development research and development (R & D) with 4-D model, because time and cost limitation is only done until development stage. Instrument of data collecting in this research is validation sheet and teacher response questionnaire as well as questionnaire response of learners. LKPD that has been developed validated by 2 validators namely lecturer of Chemistry Education FKIP UR, then tested to 15 students in SMA Negeri 9 Pekanbaru and 15 students in SMA Negeri 12 Pekanbaru. The average scores of validation of feasibility aspects of content, language, kegrafisan, and presentation of LKPD developed respectively were 95.83%, 87.5%, 97.5%, and 87.5% with an overall average of 92, 08% (valid). The mean outcome of the teacher's response questionnaire to LKPD was 85.94% (good), the average score of the limited trials conducted in 2 schools were 90.56% (good) and 87.08% (good) respectively.Keywords : Development, LKPD, Learning Cycle 5-e, Rate of Reaction